Non-functionalized oil palm waste-derived reduced graphene oxide for methylene blue removal: Isotherm, kinetics, thermodynamics, and mass transfer mechanism - Ab Aziz, Nur Azrie Hizad; Md Ali, Umi Fazara; Ahmad, Anis Atikah; Mohamed Dzahir, Mohd Irfan Hatim; Khamidun, Mohd Hairul; Abdullah, Muhammad Faiq (King Saud University, 2023)
The discharge of colored effluents from industries is one of the significant sources of water pollution. Therefore, there is a growing demand for efficient and low-cost treatment methods. An adsorption process with reduced graphene oxide (rGO) synthesized using a novel double carbonization and oxidation method from the natural precursor of oil palm empty fruit bunch (OPEFB) as adsorbent is a promising approach for addressing the problem. In this study, OPEFB biochar was mixed with ferrocene with a ratio of 5:1 (m/m) and oxidized under nitrogen flow at a temperature of 300 C for 20 min, which resulted in 75.8 wt% of yield. The potential of the synthesized rGO as an effective adsorbent for dye removal from water and wastewater was explored using methylene blue (MB) as a model. Several factors were investigated, including adsorbent dosage, initial concentration, contact time, and pH, to obtain the optimum adsorption condition through batch studies. The physical and chemical characteristics of the rGO in terms of functional groups surface morphology, elemental composition, and crystallinity phase were determined through characterization. The nonlinear isotherms were appropriated using several error functions to describe the adsorption isotherm with a maximum adsorption capacity of 50.07 mg/g. The kinetic study demonstrates that MB’s adsorption fits the PFO kinetic model and agrees with Bangham’s interpretation of pore diffusion. The adsorption mechanism was found to be physisorption on the multilayer heterogeneous surface of the rGO involving p-p interaction, hydrophobic association, and electrostatic interaction. The thermodynamics study showed that the process was spontaneous and exothermic. The mass transfer mechanism study shows that the adsorption is controlled by intraparticle diffusion and involves complex pathways. The study found that the novel non- functionalized rGO could remove cationic dyes from water and wastewater.